The third dose of mRNA SARS-CoV-2 vaccines enhances the spike-specific antibody and memory B cell response in myelofibrosis patients - Fiorino, Fabio; Ciabattini, Annalisa; Sicuranza, Anna; Pastore, Gabiria; Santoni, Adele; Simoncelli, Martina; Polvere, Jacopo; Galimberti, Sara; Baratè, Claudia; Sammartano, Vincenzo; Montagnani, Francesca; Bocchia, Monica; et al. (Frontiers in Immunology, 2022)
Vaccination against SARS-CoV-2 using mRNA-based vaccines has been highly recommended for fragile subjects, including myelofibrosis patients (MF). Available data on the immune responsiveness of MF patients to mRNA SARS-CoV-2 vaccination, and the impact of the therapy with the JAK inhibitor ruxolitinib, are still fragmented. Here, we profile the spike-specific IgG and memory B-cell response in MF patients, treated or not with ruxolitinib, after the second and the third dose of SARS-CoV-2 BNT162b2 (BioNTech) and mRNA-1273 (Moderna) vaccines. Plasma and peripheral blood mononuclear cells samples were collected before vaccination, post the second and the third doses and tested for spike-specific antibodies, ACE2/RBD antibody inhibition binding activity and spike-specific B cells. The third vaccine dose significantly increased the spike-specific IgG titers in both ruxolitinib-treated and untreated patients, and strongly enhanced the percentage of subjects with antibodies capable of in vitro blocking ACE2/RBD interaction, from 50% up to 80%. While a very low frequency of spike-specific B cells was measured in blood 7 days after the second vaccination dose, a strong and significant increase was elicited by the third dose administration, generating a B cell response similar to the one detected in healthy controls. Despite the overall positive impact of the third dose in MF patients, two patients that were under active concomitant immunosuppressive treatment at the time of vaccination, and a patient that received lymphodepleting therapies in the past, remained low responders. The third mRNA vaccine dose strongly increases the SARS-CoV-2 specific humoral and B cell responses in MF patients, promoting a reactivation of the immune response similar to the one observed in healthy controls.